2021
DOI: 10.51758/agjsr-01-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Knowledge, Attitude, Anxiety, and Behaviours in Medical and Non-medical Students Towards COVID-19 Vaccination: A Need for Concern Amidst the Pandemic

Abstract: Purpose: COVID-19, a pandemic declared on March 11th, 2020, makes it crucial for the whole world to control and ensure safety measures to control such infections in the future. Fear, worry, and panic remain widespread, especially among healthcare workers. We aimed to compare the knowledge, attitude, anxiety, and behaviours of medical and non-medical students towards vaccination against COVID-19. Material and Methods: We conducted a cross-sectional study for one month on the MBBS/BDS and undergraduate nonmedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A cross-sectional study conducted among the students at a tertiary care center in North India, showed that medical students had sufficient knowledge, an optimistic attitude, and moderate levels of concern towards COVID-19. Vaccine hesitancy was much lower among medical students when compared to non-medical students ( 23 ). The Coronavirus Disease 2019 (COVID-19) pandemic has persisted despite reductions in disease severity, hospitalizations and deaths since the introduction of multiple vaccines that protect against COVID-19 and pharmaceuticals to treat its symptoms ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted among the students at a tertiary care center in North India, showed that medical students had sufficient knowledge, an optimistic attitude, and moderate levels of concern towards COVID-19. Vaccine hesitancy was much lower among medical students when compared to non-medical students ( 23 ). The Coronavirus Disease 2019 (COVID-19) pandemic has persisted despite reductions in disease severity, hospitalizations and deaths since the introduction of multiple vaccines that protect against COVID-19 and pharmaceuticals to treat its symptoms ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%